2012
DOI: 10.1007/s00441-011-1300-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β3 is not critical for neutrophil recruitment in a mouse model of pneumococcal pneumonia

Abstract: Streptococcus pneumoniae is one of the most common causes of bacterial pneumonias in humans. Neutrophil migration into lungs infected with S. pneumoniae is central to the host defense but the mechanisms of neutrophil recruitment, as mediated by S. pneumoniae, into lungs are incompletely understood. Therefore, we have assessed the role of integrin αvβ3 by evaluating its subunit β3 in a mouse model of lung inflammation induced by S. pneumonia. Integrin subunit β3 knockout (β3(-/-)) and wild-type (WT) mice were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Then, the effect of ZmpC was examined in a pneumonia model in C57Bl/6 mice through infection with wild type S. pneumoniae TIGR4 or its isogenic zmpC mutant. As demonstrated before, acute pneumococcal pneumonia is accompanied by massive neutrophil influx 8 h after disease onset (Gauthier et al ., ; Kadioglu et al ., ; Janardhan et al ., ). Here, the intranasal inoculation of mice with wild type TIGR4 resulted in a significantly lower amount of neutrophils recruited to lung lumen compared with the isogenic zmpC mutant (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Then, the effect of ZmpC was examined in a pneumonia model in C57Bl/6 mice through infection with wild type S. pneumoniae TIGR4 or its isogenic zmpC mutant. As demonstrated before, acute pneumococcal pneumonia is accompanied by massive neutrophil influx 8 h after disease onset (Gauthier et al ., ; Kadioglu et al ., ; Janardhan et al ., ). Here, the intranasal inoculation of mice with wild type TIGR4 resulted in a significantly lower amount of neutrophils recruited to lung lumen compared with the isogenic zmpC mutant (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…VLA-4 also mediates a minor portion of the CD18-independent PMN trafficking to Pneumococcal pneumonia [112]. By contrast, PMN integrin β 3 is reportedly not involved in PMN recruitment to the lungs in Pneumococcal pneumonia [113]. Finally, non-integrin PMN adhesion proteins such as CD47 have also been shown to regulate PMN trafficking to the lung during E. coli pneumonia [114], as further discussed below.…”
Section: Cd18-dependent and -Independent Pmn Recruitmentmentioning
confidence: 99%
“…CD61 induces cortical actin reorganization, thus stabilizing focal adhesions ( 22 ). We and others have shown that CD61 knock-out mice, blocking antibodies and peptides like RGD amplify vascular leak, neutrophil recruitment and worsen survival in acute lung injury and sepsis models ( 23 , 24 ). Thus, CD61 is an important regulator of the alveolar barrier.…”
Section: Introductionmentioning
confidence: 99%